Features of Influence of X-radiation and Magnetic Field on the Electrical Characteristics of Barrier Structures Based on p-Si with Dislocation, Designed for Solar Energy - D.P. Slobodzyan; B.V. Pavlyk; M.O. Kushlyk (Журнал нано- та електронної фізики)
This paper reviews the influence of low doses X-rays (D < 400 Gy) and weak magnetic field (B = 0.17 T) on the I-V and C-V characteristics changes of surface-barrier Bi-Si-Al structures based on p-Si crystals with dislocation concentration > 102 cm – 2 in the surface layer of silicon. The charge accumulation in the SiO2 dielectric layer of the structures under the action of external fields was investigated and analyzed.